THE ROLE OF OLMAS UMARBEKOV'S DETECTIVE WORKS IN HIGHLIGHTING SOCIETAL ISSUES (Modern education and development, 2024)
Olmas Umarbekov’s detective works captivate readers with their intriguing mysteries while also shedding light on critical societal issues such as corruption, inequality, and moral decay. By seamlessly blending entertainment with profound social commentary, Umarbekov has established himself as a key figure in Uzbek literature. This article explores his contributions to the detective genre and their broader societal implications.O`lmas Umarbekovning detektiv asarlari nafaqat sirli va qiziqarli voqealar orqali oʻquvchilarni maftun qiladi, balki dolzarb ijtimoiy muammolarni yoritishda muhim rol oʻynaydi. Korruptsiya, tengsizlik va axloqiy buzilish kabi masalalarni oʻz asarlarida teran koʻrsatib, muallif oʻquvchilarni chuqur fikr yuritishga undaydi. Ushbu maqola Umarbekovning detektiv janrida ijtimoiy tanqidni muvaffaqiyatli uygʻunlashtirgan ijodini oʻrganishga bagʻishlangan.Детективные произведения Олмаса Умарбекова привлекают читателей захватывающими сюжетами, одновременно поднимая острые социальные проблемы, такие как коррупция, неравенство и моральный упадок. Умело сочетая развлечение с глубоким социальным анализом, Умарбеков стал значимой фигурой в узбекской литературе. Эта статья посвящена изучению его вклада в детективный жанр и его влияния на общество.